Síntese de hidrogéis superabsorventes como carreadores de herbicidas - Oliveira, Marlizia Adja Lopes de (2017)
Agriculture plays an important role in Brazil. According to data from Agriculture Ministry, the exports from Brazilian agribusiness resulted in US$ 9.13 billions in July of 2015. The use of agrochemical products is necessary to meet the agricultural demand. However, superdosages of pesticides and damages caused by some of these substances, which are toxic, mutagenic, and carcinogenic, are reasons of concern. In spite of environmental pollution caused by pesticides, the management of these chemical substances reduces expences of up to US$ 20 billion per year in the American economics. By this way, the use of agricultural inputs in crops is not the problem but the management of these chemical agents on agriculture is. As a possibility of minimizing pesticide superdosage, then reducing environmental damages, studies about superabsorbent hydrogels which acts as pesticide carriers have gained more space at scientific research. These polymers can be used as carriers, where the active principle is anchored, then it is released gradually to the media where hydrogel was inserted. In this work, superabsorbent hydrogels based on acrylamide and potassium acrylate (Pam Acryl) were synthesized and characterized. In addition, a commercial hydrogel (Forth Gel®), which has the same composition of the another one was also used as comparison. Different methodologies of incorporation of the herbicide 2,4-D onto polymeric network of hydrogel were evaluated. After analysis, it was used the best method of incorporation to work with the pesticides metribuzin and atrazine. As results, it was verified that the methodology of incorporation 3 (where 1 in 1 mL solution of the herbicide was added in a flask containing 100 mg of hydrogel until the gel swelled up) was the best one. Releasing of 2,4-D higher than 90% was obtained at water. The hydrogel Pam Acryl showed swelling hiher than Forth Gel®. Data from FTIR and MEV proved that anchoring of herbicide into hydrogels does not degrade the polymeric network. After herbicide releasing, the hydrogels keep their basic function, that is, they keep storing a great amount of water onto their polymeric matrix. At this point, it is highlighted that Pam Acryl anchored with atrazine – 10 g/L and the methodology of incorporation 3 presented an increase of 38.1% on swelling degree of hydrogel. Finally, the hydrogels Pam Acryl and Forth Gel® showed favorable results as the propose of herbicides carriers.